2004
DOI: 10.1023/b:binv.0000041555.29305.41
|View full text |Cite
|
Sign up to set email alerts
|

The Invasive Kelp Undaria Pinnatifida (Phaeophyceae, Laminariales) Reduces Native Seaweed Diversity in Nuevo Gulf (Patagonia, Argentina)

Abstract: The kelp Undaria pinnatifida (Phaeophyceae) is a seaweed native to northeast Asia, but during the last two decades, it has been accidentally or intentionally introduced in several temperate coasts worldwide. In central Patagonia (Argentina), this species was first detected in late 1992, and it is progressively spreading from the point of introduction. Through a manipulative experiment involving Undaria removal in 2001, we found that its presence is associated with a dramatic decrease in species richness and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
2
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(123 citation statements)
references
References 27 publications
1
113
2
7
Order By: Relevance
“…Colonization of natural habitats may have been facilitated by disturbance to native canopies, through storm events or anthropogenic stressors for example, as has been shown elsewhere (Valentine and Johnson, 2003;Schiel and Thompson, 2012) It is not yet known whether the presence of U. pinnatifida in the UK has detrimental effects on native flora and fauna, through increased competition for resources for example, as has been suggested in other temperate regions invaded by U. pinnatifida (Curiel et al, 1998;Casas et al, 2004). Alternatively, U. pinnatifida may have negligible effects on native macroalgae as it may occupy a different niche than native canopy formers, with minimal spatial or temporal overlap in demand for resources.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Colonization of natural habitats may have been facilitated by disturbance to native canopies, through storm events or anthropogenic stressors for example, as has been shown elsewhere (Valentine and Johnson, 2003;Schiel and Thompson, 2012) It is not yet known whether the presence of U. pinnatifida in the UK has detrimental effects on native flora and fauna, through increased competition for resources for example, as has been suggested in other temperate regions invaded by U. pinnatifida (Curiel et al, 1998;Casas et al, 2004). Alternatively, U. pinnatifida may have negligible effects on native macroalgae as it may occupy a different niche than native canopy formers, with minimal spatial or temporal overlap in demand for resources.…”
Section: Discussionmentioning
confidence: 94%
“…Research into the effects of U. pinnatifida invasions on recipient macroalgae-dominated systems has shown varying impacts on local biodiversity. Studies have shown both an increase (Irigoyen et al, 2011) and a decrease (Curiel et al, 1998;Casas et al, 2004) in local diversity as a result of U. pinnatifida introductions, as well as subtle and inconsistent effects on native species and associated assemblages (Raffo et al, 2009;South et al, 2015). It is likely that U. pinnatifida impacts are context-dependent, but it does have the potential to affect the performance and/or abundance of native kelp species within Plymouth Sound because it is an opportunistic fast-growing species that occupies a substantial area of seabed by early summer (Heiser et al, 2014), and can shade co-existing native species (Smale, pers obs.).…”
Section: Introductionmentioning
confidence: 98%
“…Así lo indican los estudios de Walker & Kendrick (1998) en Australia, Sanderson & Barret (1989) en Tasmania y Casas & al. (2004) en Argentina.…”
Section: Impacto Ambiental Y Perspectivas De Futurounclassified
“…Its unique mechanism of settlement on the outer lip of the shell aperture altered calcium deposition and often severely retarded the growth of infested individuals and economic losses to the industry were considerable (CULVER & KURIS 2000). The kelp Undaria pinnatifida (Phaeophyceae), native to northeast Asia, was first detected in late 1992 offshore in central Patagonia (Argentina) and is progressively spreading, along with a dramatic decrease in species richness and diversity of native seaweeds in Nuevo Gulf (CASAS et al 2004). These are only a few recent examples.…”
Section: Resumo Ascídiasmentioning
confidence: 99%